THE IMPACT OF SOCIAL MEDIA PERCEPTION ON TAX TRANSPARENCY AND GOVERNANCE - Annisa Fitriani; Yuniati; Lisna Lisnawati (Universitas Mercu Buana Yogyakarta, 2025)
The level of compliance among motor vehicle taxpayers in Garut Regency remains relatively low, despite government efforts to provide easier access and information through digital services. One indication of this low compliance is the high number of vehicles that have not been re-registered, which reflects the practice of tax avoidance. This study aims to examine the effect of tax knowledge, social media information disclosure, and ease of tax payment access on tax avoidance among motor vehicle taxpayers in Tarogong Kidul District, Garut Regency. This research employs a quantitative method with a descriptive approach. Data were collected through questionnaires distributed to 100 respondents selected using purposive sampling based on the Slovin formula. The data were analyzed using multiple linear regression. The results indicate that tax knowledge has no significant effect on tax avoidance when examined in isolation. In contrast, the disclosure of social media information and the ease of accessing tax payment options have a negative and significant impact on tax avoidance. Simultaneously, tax knowledge, social media information disclosure, and ease of access to tax payment have a substantial effect on tax avoidance. The implications of this study include the need to improve tax education, optimize the use of social media, develop accessible tax payment services, and expand the range of variables in future research related to tax avoidance behavior.